SOME MORPHOLOGICAL AND FUNCTIONAL CHARACTERISTICS OF THE RIGHT EXTERNAL ILIAC ARTERY IN MAINTENANCE HEMODIALYSIS PATIENTS WITH CHRONIC KIDNEY DISEASE ASSESSED BY DUPLEX ULTRASOUND - Nguyễn Duy, Toàn; Nguyen Thi Thu Ha (Tạp chí Y học Quân sự, 2025)
Objectives: To investigate some morphological and functional parameters of the right external iliac artery using Duplex ultrasound in hemodialysis patients with indication for kidney transplantation. Subjects and methods: A cross-sectional study evaluated the diameter, intima-media thickness (IMT), peak systolic velocity (Vs), end diastolic velocity (Vd) and resistance index (RI) of the right external iliac artery using ultrasound in 45 patients (patient group) on maintenance hemodialysis (MHD) awaiting kidney transplants, compared to a control group of 26 healthy individuals (control group). Results: The diameter of the right external iliac artery (4.91 ± 0.6 mm) and end diastolic velocity (2.9 cm/s) in the patient group were lower compared to the control group (5.27 ± 0.58 mm and 6.0 cm/s, respectively), p < 0.05. The intima-media thickness (1.23 ± 0.35 mm), peak systolic velocity (82.1 cm/s), and arterial resistance index (0.95 ± 0.02) in the patient group were higher than in the control group (0.82 ± 0.12 mm, 72.05 cm/s, 0.91 ± 0.04, respectively), with p < 0.05. In the patient group, the rate of patients with arterial stenosis, IMT thickening, increased Vs, decreased Vd, elevated RI, and atherosclerosis were 20%, 60%, 35.6%, 17.8%, 11.1%, and 26.7%, respectively. Arterial diameter was negatively correlated with IMT and Vs and positively correlated with Vd (p < 0.05). IMT was positively correlated with Vs and RI (p < 0.05).